Parental Digital Literacy Strategies Preventing Child Sexual Exploitation on Social Media - Maulida Azzahra; Syafrimen Syafril (International Journal of Multidisciplinary Research of Higher Education, 2026)
Child sexual exploitation in digital spaces encompasses online grooming, sextortion, child trafficking for pornography, and the production and distribution of sexual content involving minors. The rapid growth of internet and social media use among children and adolescents has intensified these risks. This study aims to systematically identify and analyze parental digital literacy strategies in preventing child sexual exploitation on social media, develop an applicable educational model, and examine supporting and inhibiting factors in its implementation. Employing a qualitative approach with a Systematic Literature Review (SLR) design, the research synthesizes relevant scholarly literature through identification, appraisal, and thematic integration. Findings reveal that digital predators exploit techniques such as grooming, emotional manipulation, and identity deception, which are difficult to detect without parental mediation. Parents with strong digital literacy act as facilitators and mediators in fostering children’s digital resilience. Three clusters of strategies are identified: technical‑operational measures, educational‑communicative approaches, and contextual factors influencing implementation. The study underscores the importance of collaboration among families, schools, and communities to establish a comprehensive child protection system in digital environments.